Breast Cancer Risk Analysis by the Use of Hormonal Contraceptives and Age of Menarche - Dewi, Gusti Ayu Triara; Hendrati, Lucia Yovita (Faculty of Public Health, 2015)
ABSTRACTThe number of cases of breast cancer is increasing every year and itâs a serious health problem in the world, including in Indonesia. Breast cancer is type of cancer that is most dominant in Indonesia. High estrogen exposure is one of factor that can increase the risk of breast cancer in women. This study was conducted to determine the relationship of estrogen exposure through the use of hormonal contraceptives and age of menarche with breast cancer incidence in women. Type of this study is observational analytic and use case control design. All of women breast cancer patients of Dr. Soetomo Hospital in 2013 were the population of case. All of woman non breast cancer patients who done breast examination at Dr Soetomo Hospital in 2013 were the population of control. The number of respondents in this study were 90 respondents were drawn from population using simple random sampling method. The variables studied were the use of hormonal contraceptives and age of menarche. The results of the analysis used binary logistic regression (Î± = 5%) indicated that the use of hormonal contraceptives (p = 0,028; OR = 3,266) and age of menarche (p =0,031; OR = 3,492) has an significant correlation with incidence of breast cancer in women at Dr. Soetomo Hospital in 2013. It is expected that the community can be more accurate in determining the duration of hormonal contraception usage and avoid lifestyle can accelerate the occurrence of menarche.Keywords: breast cancer, risk factor, hormonal contraceptives, age of Â Â Â Â Â Â Â Â Â Â Â Â Â Â menarche, estrogen